Impacto de la Calidad en la Rentabilidad - Forero, Jairo Antonio; Bohórquez Arévalo, Luz Esperanza; Lozano, Alfonso (Ingeniería, 2007)
The quality has become one of the most commonly used management tools in organizations, because it is part of the pre-Mass, which generates positive impact on the financial performance of the company.However, despite the above consideration, it is common to find in the market, companies that post to implement the quality strategy, fail to hit the finances of the organization, and worse disappear from the market.The purpose of the article is to analyze the different academic study on the relationship quality profitability and in light of these preliminary conclusion so if the quality influences or not, in the financial performance of the organization, as well as identify the factors determine the impact.Some studies show that there is a positive impact on the quality for the organization, other research argue that the quality is not profitable but necessary and ultimately others assert that this impact is only possible through the business strategy. In general the results are interesting and should be analyzed by the business sector, if the quality really impact profitability.